2016
DOI: 10.1371/journal.pone.0147885
|View full text |Cite
|
Sign up to set email alerts
|

Role of Proteolipid Protein in HSV-1 Entry in Oligodendrocytic Cells

Abstract: Herpes simplex virus type 1 (HSV-1) has the ability to enter many different hosts and cell types by several strategies. This highly prevalent alphaherpesvirus can enter target cells using different receptors and different pathways: fusion at a neutral pH, low-pH-dependent and low-pH-independent endocytosis. Several cell receptors for viral entry have been described, but several observations suggest that more receptors for HSV-1 might exist. In this work, we propose a novel role for the proteolipid protein (PLP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Previous works carried out by our group have shown that OLs are highly susceptible to HSV-1 infection ( 40 ). Subsequent works revealed that oligodendrocyte precursor cells (OPCs) and cells of the human oligodendroglial HOG cell line cultured under differentiation conditions become more susceptible to HSV-1 ( 41 ), a fact that was consistent with the later finding that PLP, a myelin protein upregulated throughout differentiation, is involved in viral entry ( 42 ). These findings support the hypothesis that OLs might be a more susceptible target of HSV-1 infection in glial cells undergoing differentiation, a fact that could be relevant in HSV-1 pathogenicity.…”
Section: Introductionsupporting
confidence: 52%
“…Previous works carried out by our group have shown that OLs are highly susceptible to HSV-1 infection ( 40 ). Subsequent works revealed that oligodendrocyte precursor cells (OPCs) and cells of the human oligodendroglial HOG cell line cultured under differentiation conditions become more susceptible to HSV-1 ( 41 ), a fact that was consistent with the later finding that PLP, a myelin protein upregulated throughout differentiation, is involved in viral entry ( 42 ). These findings support the hypothesis that OLs might be a more susceptible target of HSV-1 infection in glial cells undergoing differentiation, a fact that could be relevant in HSV-1 pathogenicity.…”
Section: Introductionsupporting
confidence: 52%
“…Dilutions of anti-dynamin 2 were prepared in the presence of 10% human serum. Controls to assess labelling specificity included incubations with control primary antibodies or omission of the primary antibodies [24].…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%
“…Additionally, a mouse monoclonal antibody against PLP drastically inhibited HSV-1 entry into HOG cells. Moreover, PLP and virions were shown to colocalize by confocal and electron microscopy analyses, suggesting that PLP might be involved in HSV-1 entry in human oligodendrocytes [20].…”
Section: Herpes Simplex Virus Type 1 Tropismmentioning
confidence: 95%
“…Several cell receptors for viral entry have been described, but numerous observations suggest that more receptors for HSV-1 might exist. In [20], a novel role for the proteolipid protein (PLP) in HSV-1 entry into the human oligodendrocytic cell line human oligodendroglioma (HOG) has been proposed. Oligodendrocytes (OLs) are the glial cells that produce myelin, the electrically insulating layer that surrounds axons in the CNS [21].…”
Section: Herpes Simplex Virus Type 1 Tropismmentioning
confidence: 99%